The species of Tigrideae (Iridaceae) in the Sierra of Nanchititla, State of México, Mexico, and description of the new species Tigridia nanchititlensis - Rodríguez, Aarón; Szeszko, Dennis; Munguía-Lino, Guadalupe (Phytotaxa, 2020)
The Sierra of Nanchititla Natural Park is located in central Mexico. It occupies the southwestern corner of the State of México, within the municipality of Luvianos at the border with the states of Michoacán and Guerrero. It is part of the Balsas Basin biogeographical province. The sierra is a topographically complex region, isolated from the neighboring sierras, harboring several endemic species. Here, Tigridia nanchititlensis is described and illustrated as a new species. Morphologically, this taxon pertains to the subgenus Hydrotaenia. It is a rupicolous and pendulous plant characterized by its horizontal flowers and upright fruits. It is most closely related to T. meleagris, and co-occurs in the studied area with other species of Tigrideae, such as Cardiostigma longispatha, Cipura campanulata, Tigridia meleagris, T. mortonii, and T. pavonia. Two of them, Tigridia nanchititlensis and T. mortonii are endemic to the Sierra of Nanchititla.